Teacher Parenting Administration: Implication on Pupils’ Academic Performance in Kenya Certificate of Primary Education in Hamisi Sub-County, Vihiga County, Kenya - Mujivane, Yidah Boniface; Ondigi, Benjamin A.; Mwebi, Bernard (International Journal of Novel Research in Humanity and Social Sciences, 2016)
The purpose of this study was to explore the Implication of Teacher Parenting Administration on Pupils’ Academic Performance in Kenya Certificate of Primary Education in Hamisi Sub-County, Vihiga County, Kenya. A descriptive survey research design was used to guide the study. The objectives that guided the study were, Find out Teacher Parenting, to find out teacher parenting styles in Hamisi Sub-County, Vihiga County, Kenya. The study population was 104 head teachers, 1683 Standard eight class teachers, 4420 Standard eight pupils and 532 Parents and a County Director of Education (CDE). Simple random sampling was used in selecting 34 head teachers while stratified random sampling technique was used to select 536 standard eight class teachers and 1734 standard eight pupils and 45 parents and saturated sampling was used to select a CDE. The data were collected using Questionnaires, in-depth interviews and document analysis. Quantitative data were analysed using descriptive statistics in the form of the percentages and means. The qualitative data were analysed according to themes and sub themes and the categories and sub-categories as they emerged from the data. The findings of the study showed that the main teacher parenting styles were: Authoritative, naturalistic and attached teacher parenting; Provision of teaching facilities, regular teacher parent conferences, The factors that favoured teacher parenting were: identification of students individual needs and addressing them, regular assessment and extra tuition for weak students, effective syllabus coverage, supervision of teachers in class, rewarding both teachers and students were effective ways of administering teacher parenting. The major challenges that faced schools in administering teacher parenting needs were: high enrolment resulting from FPE, shortage of teachers and delay in disbursement of Government funds. It was concluded that teacher parenting is critical in KCPE performance.
Keywords: Teacher Parenting Administration; parenting style; Hamisi District and implications.